2014
DOI: 10.1016/j.otsr.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of osteoarthritis secondary to partial or total arthrodesis of the subtalar and midtarsal joints after a minimum follow-up of 10 years

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
1
30
1
2
Order By: Relevance
“…The mean change was 0.7 ± 7.3 degrees (95% CI, -4.5, 5.9; P = .77). The calcaneal pitch improved from preoperatively 10.3 ± 5.7 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] degrees to 14.7 ± 4.5 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] degrees postoperatively. The significant mean increase was 4.4 ± 2.7 degrees (95% CI, 2.5, 6.3; P = .0006).…”
Section: Radiological Resultsmentioning
confidence: 99%
“…The mean change was 0.7 ± 7.3 degrees (95% CI, -4.5, 5.9; P = .77). The calcaneal pitch improved from preoperatively 10.3 ± 5.7 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] degrees to 14.7 ± 4.5 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] degrees postoperatively. The significant mean increase was 4.4 ± 2.7 degrees (95% CI, 2.5, 6.3; P = .0006).…”
Section: Radiological Resultsmentioning
confidence: 99%
“…Double and triple arthrodeses resulted in similar effect on the distribution of contact stresses. ankle have been equivocal and abnormal joint mechanics have been implicated [13,15]. Therefore, our controlled laboratory study aimed to describe and relate the biomechanical consequences of subtalar, double, and triple arthrodeses in the tibiotalar joint by applying these hindfoot fusion modalities to the same cadaveric feet and the randomizing testing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Good results were found in the majority of cases with high rates of patient satisfaction (1,5,12). Nevertheless, Ebalard et al reported that 84% of patients complained of pain after a minimum follow-up of 10 years (13). In other studies, the prevalence of osteoarthrosis ranged from 24-100% in the subtalar joint and from 18-77% in the Chopart joints (14).…”
mentioning
confidence: 98%